2017
DOI: 10.3233/blc-170120
|View full text |Cite|
|
Sign up to set email alerts
|

Tertiary Lymphoid Structures Associate with Tumour Stage in Urothelial Bladder Cancer

Abstract: Background:Urothelial bladder cancer (UBC) is a highly prevalent disease in North America, however its optimal management remains elusive. The contribution of B cell associated responses is poorly understood in bladder cancer. Lymphoid neogenesis is a hallmark of an active immune response at tumor sites that sometimes leads to formation of tertiary lymphoid structures (TLS) that resemble germinal centers formed in secondary lymphoid organs.Objective:This study was conducted with an aim to investigate the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 16 publications
(3 reference statements)
2
26
0
Order By: Relevance
“…TLTs typically elaborate functions that otherwise only occur within the secondary lymphoid organs, but TLTs are localized to the site of inflammation and immune response 15 , 16 . Lymphoid aggregates have been reported in a few models of chronic bacteriuria and bladder cancer but remain poorly characterized and have thus far not been reported in unperturbed bladders 18 , 19 , 33 . Since bTLTs are specifically found in aged bladders, they could facilitate inflamm-aging within the bladder tissue and significantly alter immune responses to a variety of stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…TLTs typically elaborate functions that otherwise only occur within the secondary lymphoid organs, but TLTs are localized to the site of inflammation and immune response 15 , 16 . Lymphoid aggregates have been reported in a few models of chronic bacteriuria and bladder cancer but remain poorly characterized and have thus far not been reported in unperturbed bladders 18 , 19 , 33 . Since bTLTs are specifically found in aged bladders, they could facilitate inflamm-aging within the bladder tissue and significantly alter immune responses to a variety of stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxic T cell response is driven by cancer-associated antigens 29 and bladder cancer ranks among cancers with the highest mutation burden. 30 In the present study, high densities of CD8 + T cells in both TURB and cystectomy specimens were found to be independently associated with a prolonged TTR.…”
Section: Discussionmentioning
confidence: 99%
“…33 The presence of lymphoid aggregates indicates an ongoing clonal B cell expansion and has gained attention due to their prognostic role in some cancers. 29,34 Lymphoid aggregates have been found to be more common in high-grade MIBC than in low-grade non-MIBC. 29 But their prognostic value has not yet been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, isolated lymphoid follicles (intestinal TLT) in aged mice have altered 58 cellular compositions and produce more IgA compared to young mice (27), and inducible 59 bronchus-associated lymphoid tissue (lung TLT) forms more robustly in response to cigarette 60 smoke in aged mice compared to young mice (28). Whether aging affects immunity in the bladder 61 mucosa is not known. Since both infectious and non-infectious chronic bladder inflammation is 62 highly prevalent in older women, age-associated disruption of immune homeostasis in the bladder 63 may mediate inflammatory pathology and lower urinary tract symptoms.…”
Section: Introductionmentioning
confidence: 99%